An efficient and accurate method for computation of energy release rates in beam structures with longitudinal cracks. (January 2015) - Blasques, J.P.; Bitsche, R.D.
Graphical abstract: Highlights: We present a method for the computation of energy release rates in beams. The method is applicable to beams with long, longitudinal cracks. A beam model and a finite element based cross section analysis tool are used. Energy release rates are computed using the Virtual Crack Closure Technique. Validation examples show that the method is accurate and very efficient. Abstract: This paper proposes a novel, efficient, and accurate framework for fracture analysis of beam structures with longitudinal cracks. The three-dimensional local stress field is determined using a high-fidelity beam model incorporating a finite element based cross section analysis tool. The Virtual Crack Closure Technique is used for computation of strain energy release rates. The devised framework was employed for analysis of cracks in beams with different cross section geometries. The results show that the accuracy of the proposed method is comparable to that of conventional three-dimensional solid finite element models while using only a fraction of the computation time.